2012
DOI: 10.1063/1.3699312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the absolute internal quantum efficiency of photoluminescence in GaN co-doped with Si and Zn

Abstract: The optical properties of high-quality GaN co-doped with silicon and zinc are investigated by using temperature-dependent continuous-wave and time-resolved photoluminescence measurements. The blue luminescence band is related to the Zn Ga acceptor in GaN:Si,Zn, which exhibits an exceptionally high absolute internal quantum efficiency (IQE). An IQE above 90% was calculated for several samples having different concentrations of Zn. Accurate and reliable values of the IQE were obtained by using several approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 21 publications
0
71
0
Order By: Relevance
“…A closed-cycle optical cryostat was used for temperatures between 15 and 320 K. The absolute internal quantum efficiency of PL η is defined as η = I PL /G, where I PL is the integrated PL intensity from a particular PL band and G is the concentration of electron-hole pairs created by the laser per second in the same volume. To find η for a particular PL band, we compared its integrated intensity with the PL intensity obtained from a calibrated GaN sample [18,19]. All samples were studied under identical conditions.…”
Section: A Experimental Detailsmentioning
confidence: 99%
“…A closed-cycle optical cryostat was used for temperatures between 15 and 320 K. The absolute internal quantum efficiency of PL η is defined as η = I PL /G, where I PL is the integrated PL intensity from a particular PL band and G is the concentration of electron-hole pairs created by the laser per second in the same volume. To find η for a particular PL band, we compared its integrated intensity with the PL intensity obtained from a calibrated GaN sample [18,19]. All samples were studied under identical conditions.…”
Section: A Experimental Detailsmentioning
confidence: 99%
“…PL decay after a pulsed excitation is nonexponential at low temperatures because DAP-type transitions dominate, and the separations in these pairs are random, the decay of the GL2 band is exponential for a wide range of temperatures (15-100 K), with a characteristic PL lifetime of about 0.3 ms. To explain this unusual behavior, Reshchikov et al (2014a) suggested that the observed GL2 band is caused by an internal transition, whereby the weakly localized electron collapses to the localized orbital, and the center converts from V 2 + N to V + N . The PL quenching with an activation energy of $100 meV in the temperature range of 100-200 K is attributed to the thermal emission of electrons from the 0/+ level of V N to the conduction band, whereas the PL quenching with an activation energy of $400 meV at higher temperatures is attributed to the thermal emission of holes from the +/2+ level to the valence band.…”
Section: Rl (181 Ev) Band In Undoped Ganmentioning
confidence: 96%
“…Such high Huang-Rhys factors (S g ¼ 24, S e ¼ 26.5) and small characteristic phonon energies (ℏΩ e ¼ 23meV and ℏΩ g ¼ 21meV) are typical for deep donors (Alkauskas et al, 2012). Reshchikov et al (2014a) have attributed the GL2 band to the isolated nitrogen vacancy, V N . While for a majority of PL bands in n-type GaN, the The RL2 and GL2 bands in GaN at T ¼ 18 K and P exc ¼ 1 mW cm À2 .…”
Section: Rl (181 Ev) Band In Undoped Ganmentioning
confidence: 97%
See 2 more Smart Citations